(untitled) (Journal of Energy and Safety Technology (JEST), 2024)
Finding the optimal design method for offshore wind turbines in wind farms poses a challenge due to various optimization considerations. This study addresses the optimization problem of wind turbine placement using the Greedy Algorithm. The problem incorporates a linear wake model and a power output function, with an incremental computation method devised to account for the impact of additional turbines on existing ones, thereby enhancing the wind power assessment process. The objective function of the proposed study is the power output, factoring in the wake effect from nearby turbines. The optimal wind farm layout is determined through two optimization stages applied to the existing designs. The proposed wind farm aims to generate 3 MW of power from the turbines. Two scenarios with constant wind velocities and different rotor diameters were utilized to test the proposed method, employing Ansys 2022 as the simulation software. The findings demonstrate that the proposed Greedy Algorithm, coupled with repeated adjustments, yields more accurate results. By optimizing the placement of turbines while considering their mutual influence on power output, the proposed method validates the effectiveness of the Greedy Algorithm for wind turbine position optimization. The insights gained from this research can serve as a foundation for future work in large-scale offshore wind energy projects, contributing to the global transition toward sustainable energy solutions.